Results of quantitative and qualitative analyses of traditional prescription “Lonlunsemberu-13” - Tsagaanbaatar, Nyamdemberel; Chimedtseren, Chimedragchaa (Proceedings of the Mongolian Academy of Sciences, 2020)
Traditional prescription Lonlunsemberu-13 has been widely used in traditional Mongolian medicine to treat gastro intestinal dyspepsia. The purpose of this study was to determine biologically active substances in the Traditional prescription Lonlunsemberu-13 as a primary research. We screened for phenolic compounds, flavonoids, coumarins and alkaloids using a TLC method, and then we have determined those biologically active substances content by the UV/Vis spectrophotometric method. We identified the gallic acid, rutin, quercetin, apigenin, luteolin, isofraxidin and piperine in the traditional prescription. The result revealed that “Lonlunsemberu-13” consisted 4.38% ±1.9 of total phenolic compounds, 0.63% ±0.17 flavonoids, 2.45% ±0.28 of coumarins and 0.83% ±0.064 alkaloids.